Referral for CT brain in adult patients with head injury : are Emergency Centre doctors adhering to the Western Cape head injury guidelines - Moiloa, D. N. (2017)
ENGLISH SUMMARY : Background: Head injuries constitute a large number of trauma cases due to high rates of interpersonal, motor vehicle accidents, falls and use of recreational substances. The Western Cape head injury guidelines were developed to guide EC doctors with the management of acute head trauma. Objective: To investigate whether emergency centre doctors in the Western Cape are guideline-compliant when referring adult patients with head injury for CT head scans. Secondarily, we reviewed the difference in CT head referral rates during working hours and after-hours. Methodology: A retrospective chart review was performed over six months (January to July 2011) at the five local public hospitals with CT scan facilities (Groote Schuur, Tygerberg, GF Jooste, New Somerset, Paarl). Trauma and emergency centre admission records, radiology and electronic records were used to locate suitable subjects. RESULTS: 882 charts were reviewed, 77 % males and 23% females. The average age was 24 years for both genders. Results showed that NSH, GFJ & Paarl were more likely to adhere to WCHI guidelines than central hospitals during working hours (81% and 59% respectively). Guideline compliance after-hours at TBH and GSH was 73%, almost similar to rates at NSH,GFJ & Paarl. The after-/working hours ratio of CT head scan at GSH and TBH was 1.05 and 1.18 respectively. Conclusion: Doctors working at GFJ, NSH and Paarl hospitals are adhering to the WCHI guidelines more stringently than those working at GSH and TBH. Compliance rates are higher at central hospitals after-hours, during which time a lot more scans are performed.